Market structure and risk taking in the banking industry - Oz Shy; Rune Stenbacka (Bank of Finland, 1998)
This study demonstrates that the common view, whereby an increase in competition leads banks to increased risk taking, fails to hold in an environment where consumers can choose in which bank to make a deposit based on their knowledge of the riskiness incorporated in the banks' outstanding loan portfolios.We show that, in the absence of deposit insurance, competition between differentiated banks will increase the returns from diversification.We offer a welfare analysis establishing that introduction of competition into the banking industry can only improve social welfare.However, competition cannot always guarantee that diversification will occur to a socially optimal extent.Finally, we show that deposit insurance would eliminate the beneficial effects of banks competing with asset quality as a strategic instrument.
URN:NBN:fi:bof-20140807452
Keywords: 330; Risk taking in banking; banks' portfolio diversification; bank competition; deposit insurance